Tendências na incidência de tuberculose no Brasil : comparação entre diferentes regiões e grupos etários - Brust, Marília Comissoli (2015)
Objective: in this study, the trends in incidence of tuberculosis (TB) were evaluated using data from DATASUS that include all TB data available in the national system for the period between 2001 and 2012. Methods: this study is a retrospective analysis of data from DATASUS. Data were obtained from the database DATASUS through the Health Information section. Code "tuberculosis" was used to select key data on the results of the study, from 2001 to 2012. There were two selected age groups: children and adolescents aged 0-19 years and adults over 20. It was estimated the annual incidence per 100 000, which was calculated dividing the number of cases per population estimate of the age groups, obtained from the Brazilian PNAD and Census 2010 for all years studied, respectively, and multiplying the result by 100,000. Results: incidence rates showed a reduction when analyzed in the group of adults. However, no significant reduction was observed in the group of children and adolescents. Also, when we conduct regional comparisons, the north and the state of Rio Grande do Sul have shown high incidence rates. Conclusions: it would be important to improve policies for diagnosis and treatment of pediatric patients. The northern, Rio de Janeiro and the RS should be considered priority areas in fighting against TB in Brazil.